Whole‐body magnetic resonance imaging as surveillance for subsequent malignancies in preadolescent, adolescent, and young adult survivors of germline retinoblastoma: An update. Issue 7 (9th May 2020) - Friedman, Danielle Novetsky; Hsu, Meier; Moskowitz, Chaya S.; Francis, Jasmine H.; Lis, Eric; Fleischut, Megan Harlan; Oeffinger, Kevin C.; Walsh, Michael; Tonorezos, Emily S.; Sklar, Charles A.; Abramson, David H.; Dunkel, Ira J.
Abstract: Background: Germline retinoblastoma (Rb) survivors are at lifelong risk for developing subsequent malignancies (SMNs). Optimal surveillance modalities are needed to detect SMN at an early stage in this high‐risk cohort. We investigated the use of rapid whole‐body magnetic resonance imaging (WB‐MRI) as a noninvasive screening modality in this cohort. Procedure: WB‐MRI was performed in asymptomatic preadolescent, adolescent, or young adult survivors of germline Rb from February 1, 2008 to December 31, 2018 at a tertiary cancer center. We calculated sensitivity and specificity of WB‐MRI and rate of false‐positive findings requiring additional evaluation. Results: Overall, 110 WB‐MRI were performed in 47 germline Rb survivors (51% female; median age at initial WB‐MRI: 15.5 years [range 8‐25.3]). Patients received 1‐10 annual WB‐MRI examinations (median: two). Thirteen patients had an abnormal WB‐MRI; three findings were deemed to be likely benign and were not evaluated further. Ten patients required dedicated imaging and three required biopsy; two patients were diagnosed with localized high‐grade osteosarcoma, while the other eight had benign findings. One patient was diagnosed with secondary osteosarcoma 3 months after normal WB‐MRI. In total, there were 96 true negatives, 11 false positives, two true positives, and one false negative. The sensitivity of WB‐MRI in this cohort was 66.7% (95% confidence interval [CI], 14.2‐96.0) and the specificity was 89.7% (95% CI, 83.6‐93.7). Conclusions: Based on our 10‐year experience, surveillance WB‐MRI appears to have limited utility as a surveillance modality for SMN in germline Rb survivors. Alternate screening modalities should be investigated.